2019
DOI: 10.3389/fnins.2019.01038
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Facial Expression Recognition in Earthquake Witnesses

Abstract: Major adverse events, like an earthquake, trigger different kinds of emotional dysfunctions or psychiatric disorders in the exposed subjects. Recent literature has also shown that exposure to natural disasters can increase threat detection. In particular, we previously found a selective enhancement in the ability to read emotional facial expressions in L’Aquila earthquake witnesses, suggesting hypervigilance to stimuli signaling a threat. In light of previous neuroimaging data showing that trauma exposure is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…While task-based brain imaging studies indicate that PTE exposure may modulate the functional brain in meaningful ways [ 39 , 40 ], the majority of resting-state fMRI (rsfMRI) studies have examined the role of PTSD symptoms, and only a few have considered the specific effects of trauma exposure itself irrespective of PTSD. For example, studies that examined the effects of repeated trauma exposure observed altered functional connectivity between the SN and DMN in firefighters [ 41 ], and DMN and visual networks in earthquake survivors [ 42 ]. In a study of survivors of intimate partner violence, comparisons between those with and without PTSD showed no differences in intrinsic connectivity patterns 3 weeks or 6 months following assault [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…While task-based brain imaging studies indicate that PTE exposure may modulate the functional brain in meaningful ways [ 39 , 40 ], the majority of resting-state fMRI (rsfMRI) studies have examined the role of PTSD symptoms, and only a few have considered the specific effects of trauma exposure itself irrespective of PTSD. For example, studies that examined the effects of repeated trauma exposure observed altered functional connectivity between the SN and DMN in firefighters [ 41 ], and DMN and visual networks in earthquake survivors [ 42 ]. In a study of survivors of intimate partner violence, comparisons between those with and without PTSD showed no differences in intrinsic connectivity patterns 3 weeks or 6 months following assault [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…This seems particularly interesting here, since our sample of earthquake survivors, although showing signs of maladaptive responses such as sleep disorders and anxiety-related responses [ 11 ], never developed a psychopathological condition. Indeed, the L’Aquila earthquake survivors’ visual systems showed changes relating to enhanced visual processing of threat-related stimuli (i.e., emotional faces), implying hyperarousal and hypervigilance to threat [ 13 ]. Here we could observe structural changes in the left mediodorsal thalamus, a crucial relay station in the processing of relevant, potentially threatening visual stimuli and driving effective emotional regulation responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, a certain percentage of individuals can develop behavioral and emotional changes representing subclinical pathological conditions [ 9 , 11 , 12 ]. Recently, Pistoia et al [ 13 ] described a selective enhancement in the ability to read emotional facial expressions in L’Aquila 2009 earthquake survivors, suggesting hypervigilance to stimuli signaling a threat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies, including our own work following the Canterbury earthquakes, have found that when compared with non-exposed controls, exposed individuals (including those without PTSD) had increased sensitivity for cues of potential threats, including emotional facial expressions, which could help interpret potentially harmful situations rapidly and may therefore, in the short term, be a useful adaptive response. 1820…”
Section: Brain Functioning and Resiliencementioning
confidence: 99%